RNA Extraction from Plant Tissue with Homemade Acid Guanidinium Thiocyanate Phenol Chloroform (AGPC). Issue 1 (25th January 2022) - Zepeda, Baltasar; Verdonk, Julian C.
Abstract: Gene expression studies are a powerful technique to study biological processes, and isolating RNA that is pure, intact, and in sufficient amounts for downstream applications is key. Over the years, the field has moved to the use of commercial kits and ready‐made extraction buffers for RNA isolation. This became particularly problematic during the COVID‐19 crisis when supply chains were affected and when RNA extraction and analysis reagents were suddenly scarce at a time when they were particularly required. Acid guanidinium thiocyanate‐phenol‐chloroform (AGPC) is one of the oldest RNA extraction solutions, in use since 1987. It is known as a ready‐made solution, sold under different brand names, and is typically the most expensive reagent in the RNA extraction process. In this article, we describe how to prepare a low‐cost homemade AGPC solution and provide tips on how to use it for obtaining high‐quality RNA, as well as describe possible modifications for different conditions. The protocol is based on a phase separation, where RNA is maintained in the aqueous phase and DNA and proteins remain in the interphase and organic phase. After cleaning, precipitation, and resuspension steps, the RNA is ready to be quantified and used for downstream applications. By following this protocol, good yields of high‐quality RNA can be obtained from a wide variety of tissues and organisms, and we exemplify the approach here using plant tissues. Some plant tissues contain extra interferents (such as sugars), and for high‐quality RNA isolation from those tissues, an alternate protocol is provided. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : RNA isolation with homemade acid guanidinium thiocyanate‐phenol‐chloroform (AGPC) Alternate Protocol : RNA isolation from high carbohydrate‒containing tissues using an NTES‐AGPC combination